Efektivitas Kebijakan Stimulus Perekonomian Terhadap Kredit Bermasalah (Non Performing Loan ) Pada BPR Konvensional Di Bandung Dalam Masa Pandemi - Fitriawati, Fitriawati; Chandra, Ferry; Pratiwi, Astria Noer (Banking & Management Review, 2022)
Since the beginning of March 2020, Indonesia has been shocked by the COVID-19 pandemic. The spreading of virus are so fast, resulting in the increasing number of Covid-19 cases that create an effect on Indonesia’s economy, especially on the debtors performance and capacity, including debtor’s business. To encourage the optimization of the bank’s intermediation function, securing financial system stability, and supporting economic growth, an economic stimulus policy from the Financial Services Authority (OJK) is required. This stimulus was given to debtors that were affected by Covid- 19 pandemic. With the relaxation of loans and delays in payment of instalment and interest, the quality of restructured credit or financing are determined to be smooth and excepted from accountancy implementation, thus banks are not required to establish a reserve allowance for possible losses on productive assets.. This study aims to determine the effectiveness of OJK’s stimulus method to supress the non-performing loans (NPLs) in Financial Services during the pandemic. The method used in this research is descriptive quantitative method and verification using secondary data analysis approach. Data analysis used a paired sample t test (paired sample t test). Hypothesis that was measured are NPLs before the pandemic, and NPL after the stimulus was implemented, with hope that there will be no increased value on NPL. The results show the NPL average value before stimulation was implemented are higher, which means that the relaxation of credit stimulation does not effect on reducing the value of non-performing loans (NPL) significantly because debtors are reluctant to participate in a program that includes delayed payments of principal and interest, that eventually will burden the debtor.